Safety and Efficacy of Saccharomyces boulardii for the management of Diarrhoea in Indian children (International Journal of Scientific Research and Management (IJSRM), 2018)
Objective: S. boulardii seem to be an assuring biotherapeutic agent for the amelioration of the course of diarrhoea in children when used therapeutically. S. boulardii mediates responses resembling the protective effects of the normal healthy gut flora. Our objective was to access the safety and efficacy of S. boulardii on childhood diarrhea. Methodology: Total 210 patients were enrolled out of which 184 patients completed the study S. boulardii sachets (5 million CFU 282.5mg) were given to the patients enrolled in the study. Efficacy and safety assessment was made by quantitating the Frequency, Intensity and Consistency of stools. Results: Stool frequency decreased from 9.005 to 2.7 at the end of 5 days. Severity scale was extrapolated which interestingly showed zero patients with severe diarrhoea. There was a reduction in the duration of diarrhoea along with stool consistency where in majority patients with watery stool came down to 2 from 136. Conclusions: Saccharomyces boulardii is safe and efficacious in the treatment of diarrhoea in Indian children